A simple and easy to perform synthetic route to functionalized thienyl bicyclo[3.2.1]octadienes - Vuk, Dragana; Škorić, Irena; Milašinović, Valentina; Molčanov, Krešimir; Marinić, Željko (Beilstein Journal of Organic Chemistry, 2020)
In order to prepare novel polycyclic derivatives of bicyclo[3.2.1]octadiene systems fused with a thiophene ring, photochemical cyclization and aldol condensation reactions were carried out. The starting substrates were easily obtained by a Vilsmeier–Haack reaction of bicyclo[3.2.1]octadiene thiophene derivatives with dimethylformamide. From the obtained carbaldehydes, novel methyl, methoxy, and cyano-substituted styryl thienobenzobicyclo[3.2.1]octadiene derivatives were synthesized through Wittig reactions and subjected to photochemical cyclization, in terms of obtaining the new annulated structures. As part of this study, the aldol reaction of the starting 2-substituted carbaldehyde with acetone was also performed, which produced the thieno-fused benzobicyclo[3.2.1]octadiene compound with an extended conjugation.
Keywords: bicyclo[3.2.1]octadiene; photocyclization; thiophene; Vilsmeier–Haack reaction; Wittig reaction